Optimizing urban agriculture in empowering HIV/AIDS children in Lentera houses: Optimalisasi pertanian perkotaan dalam pemberdayaan anak-anak HIV/AIDS pada rumah Lentera - Pamungkas, Hanung; Ardy Prasetya, Hernowo; Autentika May Putra Pratama, Febian; Arifah, Siti; Oktiviani Pradita, Annisa; Sumarmi (Fakultas Teknologi dan Industri Pangan Unisri Surakarta, 2025)
HIV (Human Immunodeficiency Virus) is a virus that attacks a person's immune system, often called PLWHA (People with HIV AIDS). The public stigma about PLWHA has a negative impact on development, especially PLWHA who are still children, such as those at the Lantern Foundation, especially since the Lantern Foundation is located in the middle of an urban area, meaning they have to survive with the help and assistance of generous people. Urban Farming or Urban Agriculture offers an interesting and enjoyable method with the main aim of meeting food needs independently and effectively considering that land in urban areas is increasingly limited. Our implementation method uses an offline method/going directly into the field. There are various methods or types of urban farming that can be tried, such as verticulture methods, hydroponics, fish farming in bucket, using used goods as media, and seeding techniques. It is hoped that the urban farming method that we apply will entertain PLWHA children at the Lantern Foundation as a form of community service. This form of optimizing urban agriculture also indirectly trains their creativity.